Evaluasi Tawaran Kerjasama Kemitraan dengan Go-Mart dari Sudut Pandang Konsumen dan Usaha Retail di Kota Bandung - Angela Caroline; Budi Tjahja Halim (STIE Indonesia Banking School, 2016)
This study aimed to describe response of public and retail stores in the Bandung city about cooperation (partnership) conducted by Go-Mart which is a business unit of PT. Go-Jek Indonesia. The research method used was case study (about Go-Mart), which interview and survey was conducted on retail store and people in Bandung. The data analysis technique used was describe the survey result (diagram) and NMAx. The calculation result (Nmax) is used as a consideration for feasibility cooperation. In addition, the willingness of society to make purchases using Go-Jek and willingness retail stores to join with Go-Mart be other factors that are discussed in this study. This study also conducted an analysis of the feasibility of cooperate between retail store and PT. Go-Jek Indonesia (Go-Mart). This study is limited to objectives, activities, and cash flows of the partnership were probably carried out by retail business with Go-Mart. Development model of financial planning analysis is done in order to help retail businesses to decide to join the Go-Mart or not. In addition, this design also helps Go-Mart to determine the exact costs to be imposed on its partners.